Carving out legacy assets: A successful tool for bank restructuring? - Martin Hellwig (Max Planck Institute for Research on Collective Goods, 2017)
Beginning with the proposal by Enria (2017), the paper discusses the scope for successful bank restructuring through a carveout of impaired assets and a transfer of these assets to a government-sponsored asset management company. The paper argues that the success of such an operation requires a use of public funds, either outright or through contingent commitments. Clawback provisions are problematic because they create contingent liabilities that merely shift risks from the assets side to the liabilities sides of banks' balance sheets. The paper distinguishes between asset impairments coming from considerations of prospective returns and asset impairments coming from frictions in the markets in which these assets are traded. It also distinguishes between threats to bank solvency and threats to bank funding/liquidity. In each case, the success of bank restructuring from asset carveouts depends on the extent to which threats to the bank's solvency is eliminated. If these threats concern bank funding and asset liquidations at depressed prices, public funds may eventually not be needed. If threats to bank solvency come from nonperforming loans, taxpayer support may be essential. The notion of "real economic value" as the price at which assets should be transferred is problematic and leaves ample room for hidden subsidies. The success of restructuring of the individual bank may itself come at a risk to financial stability as the preservation of existing capacities maintains competitive pressure and depresses bank profitability. Additional risks may come from the burden on the government's fiscal stance.
Keywords: 330